Valorization of waste pharmaceutical residues via pyrolysis: Simultaneous production of biochar for Cd2+ removal and high-quality bio-oil/syngas - Zhizhen Feng; Bo Fu; Shanshan Han; Hong Yan; Puyang Feng; Wenxiao Li; Tao Qin; Tongtong Wang; Xinjie Zhang; Junchao Jia (PLoS ONE, 2026)
For the efficient utilization of pharmaceutical waste resources, tuber biochar (TB) and herbal biochar (HB) were prepared via oxygen-limited slow pyrolysis at 500 °C for 3 h, using residues from tuber-type Xinsuning capsule and herbal-type Changyanning pill as the raw materials, respectively. The biochars were characterized by FESEM, BET, XRD and FTIR, and the feedstock physico-chemical properties were measured by common agricultural chemical analysis methods. The results revealed that both biochars possessed a high percentage of elemental O, a honeycomb-like porous structure, and surfaces enriched with functional groups such as hydroxyl, carboxyl, and carbonyl. HB exhibited a larger specific surface area and pore volume than TB, making it a more recommended carbon material. The chemical compositions of the pyrolysis by-products were systematically analyzed. The bio-oils were rich in ketones, alkanes, alcohols, olefins, fatty acids, phenols, and heterocyclic compounds, identifying them as potential sources of liquid fuels and chemical feedstocks. The most abundant components in bio-oils from tuber and herbal biomass were “Ethanol, 2,2-diethoxy-” (7.25%) and “Phosphonic acid, (p-hydroxyphenyl)-” (10.52%), respectively. The syngas has a low hydrogen content, is mainly pyrolysis off-gas and therefore has a limited application potential. Furthermore, the environmental application for Cd²⁺ removal was critically evaluated. Adsorption isotherms demonstrated high adsorption capacities, well-described by the Freundlich model ( R ² ≥ 0.99), indicating multilayer adsorption. The maximum adsorption capacities for TB and HB were 188.89 and 186.67 mg·g⁻¹, respectively. Kinetic studies revealed that the adsorption process followed the Elovich model ( R ² ≥ 0.98), suggesting heterogeneous diffusion, with HB achieving a higher equilibrium capacity (85.67 mg·g⁻¹) than TB (73.70 mg·g⁻¹). In conclusion, pyrolysis, particularly using herbal biomass, presents a promising strategy for the comprehensive and high-value utilization of waste pharmaceutical residues, simultaneously producing effective adsorbents for heavy metal remediation and valuable bio-energy products.